From Concepts to Realities -- Promising Nanotech Applications for Agriculture, Food & Water Safety in Developing Countries - Gruère, Guillaume P. (2011)
IFPRI Policy Seminar "From Concepts to Realities Promising nanotech applications for agriculture, food and water safety in developing countries" by Guillaume Gruere on 14 November 2011